2009
DOI: 10.1037/a0013152
|View full text |Cite
|
Sign up to set email alerts
|

Embedding reading comprehension training in content-area instruction.

Abstract: This study evaluated the effectiveness of comprehension training embedded in a program that taught science content to 2nd graders. The program included instruction about the structure of compare-contrast expository text, emphasizing clue words, generic questions, graphic organizers, and the close analysis of well-structured text exemplars. This program was compared with a program that focused on the science content but included no compare-contrast training as well as with a no-instruction control. Regular clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 76 publications
2
103
0
5
Order By: Relevance
“…In light of numerous studies and theoretical frameworks asserting the important role of children's language skills to their achievement of skilled reading comprehension (e.g., Cain et al, 2004;Connor et al, 2004;Perfetti, 2007;Williams et al, 2009), an emerging body of work is focused specifically on identifying effective ways to improve children's language skills within classroom instruction. Logically, we can speculate that enhancing children's exposure to high-quality language-focused comprehension instruction in P-3 is a worthy route to improving language skills in the short term and reading comprehension in the longer term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of numerous studies and theoretical frameworks asserting the important role of children's language skills to their achievement of skilled reading comprehension (e.g., Cain et al, 2004;Connor et al, 2004;Perfetti, 2007;Williams et al, 2009), an emerging body of work is focused specifically on identifying effective ways to improve children's language skills within classroom instruction. Logically, we can speculate that enhancing children's exposure to high-quality language-focused comprehension instruction in P-3 is a worthy route to improving language skills in the short term and reading comprehension in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…Williams and colleagues, for instance, examined the effects of an explicit text-structure program as implemented by second grade teachers (Williams, Stafford, Lauer, Hall, & Pollini, 2009). The program featured reading, discussing, and analyzing expository texts as coupled with explicit teaching of how to navigate various text structures (e.g., cause/effect texts, compare/contrast texts) and how to understand clue or signal words important to navigating texts (e.g., because, since and therefore for cause-effect texts).…”
Section: Improving Language-focused Comprehension Instruction In Primmentioning
confidence: 99%
See 1 more Smart Citation
“…Meyer (1981) reported, "It is the structure of text that primarily differentiates text from simple lists of words or sentences" (p. 7). Informational text structures are conventionally identified as description, sequence, problem/solution, compare/contrast, and cause/effect (Meyer, 1979;Meyer & Poon, 2001;NGA Center & CCSSO, 2010;Williams, Stafford, Lauer, Hall, & Pollini, 2009). …”
mentioning
confidence: 99%
“…Research supports the use of informational text which include the embedded text structures (Duke & Bennett-Armistead, 2003;Hall, Sabey, & McClellan, 2005;Moss, 2005;Purcell-Gates, Duke, & Martineau, 2007;Reutzel, Read & Fawson, 2009). Some research related to text structure has been shown to help students comprehend informational text, (Rosenshine & Meister, 1994;Klingner, Vaughn & Schumm, 1998;Guthrie, VanMeter, McCann, et al, 1996, Ciardiello, 2002Williams, Stafford, Lauer, et al, 2009) text types were compare and contrast, cause and effect, and problem and solution. 4.…”
Section: Significance Of the Studymentioning
confidence: 99%